Perspectives of stakeholders on enhancing access to self-injectable contraception in rural South Sudan - Grace W. Kimemia; Mamothena Carol Mothupi; Lual Agok Luka; Teresia Macharia; Sidonia Akon; Alom Atak Ayom; Lual James Baak; Amijong Deng; Kadra Noor; Taban John Mark; Naoko Kozuki (Discover Public Health)
Abstract Background Although self-injectable subcutaneous depot medroxyprogesterone acetate (DMPA-SC) has demonstrated promise, there are significant barriers in promoting initiation and continued use in low-resource settings. This study sought to understand the perspectives of stakeholders on promotion of self-injectable contraception use in rural South Sudan. Methods The study was conducted in Aweil East County, South Sudan, using a descriptive phenomenological approach. We conducted 22 in-depth interviews and 4 focus group discussions with key stakeholders. The data interpretation was guided by social and behavior change self-care framework. Results The study showed that users valued the privacy of self-injecting at home, helping them overcome the sociocultural and geographical barriers. However, they faced challenges such as stigma, side effects, and family interference. The findings further showed that expanding the entry points for self-injectable contraception within the community by involving community health workers (CHW) as providers has the potential to reach a wider audience, including first-time users and marginalized groups. Stakeholders emphasized the need for champions to create awareness of self-injectable contraception, particularly involving community leaders, women-led organizations, and community gatherings. In addition, the users’ continuous training and supportive social networks were crucial for successful implementation. Conclusion Enhancing access to self-injectable contraception requires a multi-faceted approach that prioritizes the perspectives of stakeholders. Support from stakeholders is crucial for user awareness and continued use, while training users to ensure effective self-injectable. This collaborative approach holds the potential to address the complexities surrounding contraception access in rural South Sudan, leading to improved reproductive health for the community.